2021
DOI: 10.3389/fenvs.2021.679530
|View full text |Cite
|
Sign up to set email alerts
|

Source-Specific Patterns of Marine Debris and Associated Ecological Impacts in the Red River Estuary of Xuan Thuy National Park, Vietnam

Abstract: Vietnamese rivers are among the top ten contributors of anthropogenic debris to the ocean. However, there is limited empirical research documenting debris and its effects in Northern Vietnam. The goal of our research was to conduct the first baseline assessment of anthropogenic debris in the Red River. We aimed to understand the sources, accumulation patterns, and ecological effects of anthropogenic debris in the Red River (Song Hong) estuary. To assess debris patterns, we conducted standing stock debris surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…In Indonesian mangroves, four indicators of tree health were negatively correlated with debris density [39]. Similarly, three indices of mangrove health decreased with increasing amounts of debris, although only non-significantly, with variation explained ranging from 6% to 13% [43]. Observations further suggest that plastic debris hindered photosynthesis, smothered and thus suffocated pneumatophores, led to root deformation, disrupted aeration and water movement, which can lead to decreased soil quality, and directly sacrificed mangrove trees, particularly seedlings, because plastics physically broke down seedlings [39,[44][45][46][47][48][49][50][51].…”
Section: Macroplasticsmentioning
confidence: 92%
See 1 more Smart Citation
“…In Indonesian mangroves, four indicators of tree health were negatively correlated with debris density [39]. Similarly, three indices of mangrove health decreased with increasing amounts of debris, although only non-significantly, with variation explained ranging from 6% to 13% [43]. Observations further suggest that plastic debris hindered photosynthesis, smothered and thus suffocated pneumatophores, led to root deformation, disrupted aeration and water movement, which can lead to decreased soil quality, and directly sacrificed mangrove trees, particularly seedlings, because plastics physically broke down seedlings [39,[44][45][46][47][48][49][50][51].…”
Section: Macroplasticsmentioning
confidence: 92%
“…For mangroves, we have a number of observational studies reported harm. However, to the best of our knowledge, we have so far only three correlational studies [39,43,47] and one experimental study [42] for the impacts of macroplastics and one meta-analysis for the impacts of microplastics [30]. For seagrass meadows, there were only three mesocosm experiments [67,69,70] for the impacts of macroplastics and none for microplastics.…”
Section: Brief Summary Of Ecological Harmmentioning
confidence: 99%
“…However, the method for a global scale estimation is uncertain due to lack of consideration for local conditions of each country. Other studies in Viet Nam have previously focused on riverine plastic debris [13][14][15][16]. Lack of reliable and scientific methods for marine plastic debris estimation is a knowledge gap in the action against plastic pollution in Vietnam [17].…”
Section: Introductionmentioning
confidence: 99%